Quantum study on the branching ratio of the reaction NO2+OH. - Williams, C; Pogrebnya, S; Clary, D (2007)
A reduced dimensionality (RD) approximation is developed for the title reaction which treats the angle of approach of the hydroxyl radical to the nitrogen dioxide molecule and the radial distance between the two species explicitly. All other degrees of freedom are treated adiabatically. Electronic structure calculations at the complete active space self-consistent field level are used to fit a potential energy surface (PES) in these two coordinates. Within this RD model the adiabatic capture centrifugal sudden approximation is used to calculate the high pressure limit rate constant. A correction for reflection from the PES due to rotationally nonadiabatic transitions is applied using the wave packet capture approximation. The branching ratio for the title reaction is calculated for the atmospherically significant temperature range of 200-400 K at 20 Torr without distinguishing between the conformers of HOONO. The result is k(HOONO)k(HNO(3) )=0.051 at 20 Torr and 300 K, which is in good agreement with the measured branching ratio between cis-cis-HOONO and nitric acid. This suggests that most of the different conformers of HOONO were converted to the most stable cis-cis conformer on the time scale of the measurements made.